DETERMINATION OF THE SOLUTION OF THE ITERATED HYPERBOLIC EQUATION: Представлено академіком НАН України А.О. Чикрієм - Alexandrovich, I.M.; Lyashko, S.I.; Lyashko, N.I.; Sydorov, M.V.-S. (Reports of the National Academy of Sciences of Ukraine, 2024)
Differential equations of hyperbolic type and their iterations are widely used in the study of problems related to vibration phenomena and other problems of mechanics and mathematical physics. The methods of solving such equations involve the creation of differential and integral operators. In the work, differential operators are constructed that translate arbitrary functions into regular solutions of a hyperbolic equation of the second and higher orders. The Riquet problem for the hyperbolic equation of the fourth order is solved.